Virtual Reality Application of Motor Vehicle Simulation Test for Making SIM C Mobile Based - Zulchairi Hidayat S.Kom. Zulchairi; Husaini Husaini; Hari Toha Hidayat (Politeknik Negeri Lhokseumawe, 2024)
Virtual reality technology allows a person to simulate an object that presents a visual display similar to the real world. The problem that occurs regarding this research is that many people do not know that the motor vehicle simulation test for making a SIM C, because of that many people are lazy to go to make a SIM C, and people are often confused in the driving test for making a SIM C. So the purpose of building this virtual reality application is to conduct a motor vehicle simulation test more specifically so that they can find out how the motor vehicle simulation test is to get a SIM C. Through this information media, people can interact directly with virtual reality applications to find out simulation tests that are more interesting and easy to understand. The application built displays animated objects and text on mobile android in real time, aiming to find out pass and not pass when doing this simulation from the application that has been made. Testing is done by playing this simulation which when playing the simulation we must go at a maximum speed of 30 kph if it is more than 30 kph then we will be declared a failure of the test and if the driver goes off the track or hits the obstacle it will be declared a failure. So you have to repeat from the beginning and each mistake is given a 2x chance to repeat and if the rider still fails the 3rd simulation test then the rider is declared a failure in conducting the simulation test. If the motorcyclist does not crash and successfully passes all obstacles or does not get out of the way and does not exceed the speed of 30 kph to the finish, he will pass and be entitled to a C driver's license. fps testing in the application is to see the speed of the application on mobile android and the average fps on fps is 24 - 64 fps, so from the results of the fps test using android 1, namely android 7.0 the test results are from 59.9 fps to 60.1 fps, while from testing android 2, namely android 9.0 the test results are from 59.9 to 60.1. In testing this questionnaire we will find the entire number of question values by summing them up using the Likert scale method and then based on the results of these calculations the value obtained on all questions is 81.6%, it can be concluded that the virtual reality application of motor vehicle simulation tests for making a mobile-based SIM C is very good when used by users.